2019
DOI: 10.1108/rsr-03-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

Online active-learning: information literacy instruction for graduate students

Abstract: Purpose The purpose of this paper is to describe the challenges of teaching information literacy online to graduate students and evaluate software that supports using active learning techniques. Design/methodology/approach This conceptual paper analyzes different software tools and their functionality to aid in active learning, as well as describes elements of online teaching that facilitate active learning for information literacy. Findings Although software serves as the delivery tool, there is not one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…To ensure the acquisition of information literacy skills, training consists not only of instruction but also entails practice (Parramore, 2019). Activated learning through remote exercises is more challenging to organise.…”
Section: Challenges Posed By the Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure the acquisition of information literacy skills, training consists not only of instruction but also entails practice (Parramore, 2019). Activated learning through remote exercises is more challenging to organise.…”
Section: Challenges Posed By the Pandemicmentioning
confidence: 99%
“…an exercise, a vote, a question & answer session). Such activities will positively affect the active involvement of participants (Parramore, 2019). Students may also be more likely to follow this kind of sessions, which could have a positive impact on the attendance rate of extracurricular sessions.…”
Section: Challenges Posed By the Pandemicmentioning
confidence: 99%
“…"[M]erely including them into an online-environment does not qualify it as completely active learning." 21 She suggests that online ILI needs to be delivered to students in keeping with the thinking of Anastasia Misseyanni 22 and Lorayne Robertson 23 in Active Learning Strategies in Higher Education, such that the ILI "engages the student with meaningful learning activities and allows a metacognitive process to take place where students become active contributors to the class." 24 Robertson emphasizes metacognition as "a critical skill that enables students to assess their own learning and also critically assess sources of information," 25 which harkens back to Dewey's project-based learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Summarize the three hypotheses proposed by the authors to explain why complex societies arose in Mesoamerica (hint: for a general discussion of social complexity, see Toby Evans, pp. [19][20][21][22][23][24][25][26][27][28]. How do the authors use the concept of "nuclear areas" in examining social complexity in Mesoamerica?…”
Section: Part 1: Introduction To the Researchmentioning
confidence: 99%
“…Avcı and Ergün (2019) pointed out that IL skills are significant for students who learn course content only through online means, and that information-literate students are better able to navigate and communicate in the online learning environment. In addition, Parramore (2019) indicated that most online courses on IL are designed to focus on watching a video or demonstration of database instruction, with little opportunity for students to practice or reflect. Some researchers have indicated that without appropriate strategies for online learning, students’ learning outcomes in online environments may be similar to their conventional learning outcomes and may not show any improvement; some students may even fail to achieve their learning goals because of the lack of guidance and assistance (Lin et al , 2019a).…”
Section: Introductionmentioning
confidence: 99%